Evidence of Chikungunya virus circulation in the Terai region of Nepal in 2014 and 2015. (20th November 2017) - Pandey, Kishor; Pandey, Basu Dev; Chaurasiya, Ram Rekha; Thakur, Mahesh; Neupane, Biswas; Shah, Yogendra; Ngwe Tun, Mya Myat; Morita, Kouichi
Abstract: Background: Chikungunya virus (CHIKV) infection is an emerging viral disease in Nepal, with the reported by our laboratories in 2013. Because of the similarity in signs and symptoms to dengue virus (DENV) and misdiagnosis, the under-reporting of CHIKV infection in DENV-endemic areas of Nepal is very common. The aim of the present study is to identify CHIKV infection among patients with febrile illness during the 2014–2015 outbreaks. Methods: A total of 219 serum samples were tested for CHIKV and DENV by using enzyme-linked immunosorbent assays (ELISAs) to detect immunoglobulin M (IgM) and IgG antibodies, with confirmation by a 50% focal reduction neutralization test (FRNT50 ). Results: ELISA results demonstrated that for CHIKV and DENV, 20.5% and 14.2% of samples, respectively, were positive for IgG and/or IgM and 9.6% and 5.9% were positive for IgM alone. Further, FRNT50 results confirmed that 7.3% of samples possessed neutralizing anti-CHIKV antibodies. Conclusion: We conclude that CHIKV infection is settling in Nepal as an endemic disease. It is highly recommended to strengthen the surveillance system for CHIKV and DENV to prevent possible outbreaks.